An experimental study on the effect of DC electric field on impinging flame. (15th August 2020) - Zhen, H.S.; Wang, Z.W.; Liu, X.Y.; Wei, Z.L.; Huang, Z.H.; Leung, C.W.
Abstract: This work presents an experimental study the effects of DC electric field on a laminar premixed flame which impinges on a plate. Positive DC and ground levels of voltage are applied to the plate and burner, respectively. A reverse application of the electric field is also tested. Detailed measurements are undertaken to understand the ionic wind effect on flame impingement heat transfer. Testing shows a favorable effect of positive field on flame stability, as the flame stands leaner combustion. When a sufficiently high voltage is applied, discharge occurs which breaks down the electric field. The results of thermal field testing reveal that the temperature change observed is due to flame shape distortion caused by ionic wind. It is found that ionic wind is majorly physical in nature, inducing the changes in flame stability and temperature through a force. Further, it is mainly the post-combustion part of the flame, instead of reaction zone, bears such force. Under positive field, the burner nozzle is rapidly heated by the flame. However, flame impingement heat transfer has no significant change under either positive or reverse field. It is because heat loss from the post-combustion flame to plate is less altered by DC fields. To further study the ionic wind effect, a co-flow is introduced to the flame, and the standard deviation data of flame temperature indicate that ionic wind insignificantly changes the mixing between flame and ambient air. It confirms that ionic wind is mainly a force effect, with negligible chemical effect in the scope of this work.